Upaya Penanggulangan Penganiayaan Terhadap Awak Media Dalam Peliputan Berita Di Era Digital - Merita, Enni (Sekolah Tinggi Ilmu Hukum Sumpah Pemuda, 2024)
In the digital era, the development of mass media and rapid access to information have become important pillars in the dissemination of news. However, along with this progress, the risks faced by media personnel are increasing, including the threat of violence while covering news. This research discusses efforts to combat the abuse of media personnel in carrying out journalistic duties in the digital era. The main focus of this research is the identification of the forms of abuse frequently experienced by journalists, the underlying factors, as well as the preventive and responsive measures taken by authorities, press organizations, and legal institutions. The research findings indicate that enhancing legal protection, educating journalists' rights, and utilizing digital technology for security can be significant steps in reducing the risk of abuse against media personnel.